ANALISIS PENGARUH ARUS KAS, LEVERAGE, TINGKAT PERTUMBUHAN, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP KEBIJAKAN DIVIDEN ( STUDI PADA INDUSTRI MANUFAKTUR YANG TERCATAT PADA BURSA EFEK INDONESIA PERIODE 2011-2013 ) - Surya Budiman; Harnovinsah Harnovinsah (TEKUN: Jurnal Telaah Akuntansi dan Bisnis, 2016)
ABSTRACT This study discusses the influence of free cash flow, leverage, growth rate, size of the company, and the profitability of the dividend policy. Data collection is collected in manufacturing companies listed on the Stock Exchange in 2011 - 2013 as many as 11 companies. The independent variables used is free cash flow, leverage, growth rate, size of company, and profitability. The dependent variable used is the dividend policy. The analytical method used is the normality test, multicollinearity, heteroscedasticity test, autokolerasi test, coefficient determination test, F test, t test, and linear regression analysis. The results showed that the F test that free cash flow, leverage,  growth rate,   size of company, and profitability simultaneously affect the dividend  policy. T test     results that the company's growth and profitability partially affect  the dividend policy  while free cash flow, leverage, and the size of the company partially no  effect on    dividend policy. Keywords : dividend policy, free cash flow, leverage, growth rate, size of company, and profitability.